Board of directors and earnings manipulation: evidence from regulatory change - Sattar Khan; Yasir Kamal; Muhammad Abbas; Shahid Hussain (Future Business Journal, 2022)
Abstract The purpose of this paper is to examine the effect of the board of directors’ related clauses such as independence, female director, CEO Duality and the expertise of director included in the Code of Corporate Governance 2017 (CCG-2017) on earnings management with the pre- and post-CCG-2017 analysis. This study has used the sample of 323 non-financial listed firms of the Pakistan Stock Exchange from 2015 to 2019. Data were manually collected from companies’ annual reports, and two proxies of earnings management have used: one is discretionary accruals and the other is real activity manipulation. The results of the study show that as compared to the pre-period of CCG-2017 in the post-period of CCG-2017 board independence, expertise and female inclusion has increased significantly. Moreover, board independence and financially expert directors are negatively related to discretionary accruals, while there is a positive relationship of female directors with discretionary accruals, which is also same for real activity manipulation. The findings also show that there is no relationship of board independence/outside directors and expert directors with real activity manipulation. This study recommended the CCG-2017 reforms introduced by the regulator. Moreover, we recommend that the regulator needs to augment the authentic independence of independent/outside directors in listed firms (concentrated ownership context) of Pakistan. This study adds its part in the corporate governance literature by focusing board attributes with regulatory reforms on earnings manipulation, which is lacking in the related literature in general and in Pakistan an emerging economy in particular.